DISSERTATION TITLE: EFFECT OF CUTTING PARAMETERS ON FORCE, TEMPERATURE AND WEAR OF A SINGLE POLYCRYSTALLINE DIAMOND COMPACT CUTTER ROCK INTERACTION - ABDULLAH, ABDUL HAZIM (2020)
Single Polycrystalline Diamond Compact (PDC) cutter rock interaction experiment has been performed to study the effect of cutting parameters on the cutting performance and enhance the wear-resistance of the cutter. However, previous studies applied individual parameters on the drilling performance but neglected the interaction effect between these parameters. The analysis of the interaction effect between cutting parameters is more comprehensive since the parameters in real drilling condition is changed simultaneously. Therefore, the objectives of this study are to evaluate the effect of depth of cut, back rake angle and rock properties and their interaction on cutting force and temperature of single PDC cutter and to assess the relationship between cutting force and temperature on the wear of a single PDC cutter. Experiment setup of lathe rock cutting is employed in this study.